The Role of Industry 4.0 and 5.0 in Health Emergency Management: Challenges and Opportunities - Ruggeri, Marco; Gobbi, Laura; Vinci, Giuliana (Current Aspects in Business, Economics and Finance Vol. 3, 2022)
Several epidemics and pandemics have occurred in recent years, including the most recent Covid-19, which initiated an unforeseen and unprecedented change to which all enterprises had to react quickly. This has caused a sudden acceleration in the digitalization of the economy. In managing the health emergency, technology has indeed taken a primary role in helping governments, businesses and society. Work, education and the entire economy have been supported on contact-free modes thanks to the tools and help of 4.0 technologies. The goal of the research will be to study the new challenges offered by these technologies, and how their integration can create new opportunities for managing upcoming health emergencies.